Clinical results of everolimus-eluting stents and sirolimus-eluting stents in patients undergoing percutaneous coronary intervention - Iraj Jafaripour; Mir Saeid Ramezani; Kamyar Amin; Naghmeh Ziaie Amiri; Mohammad Taaghi Hedayati Godarzi; Fahimeh Elhaminejad; Hemmat Gholinia Ahangar (Babol University of Medical Sciences, 2023)
Background: It has been pronounced that everolimus-eluting stent (EES) had lower charge of goal-lesion revascularization and stent thrombosis as compared with sirolimus-eluting stents (SES).The goal of this observation was to compare the efficacy and protection of EES with SES in primary percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). Methods: In this retrospective study, a total of 404 patients with coronary artery stenosis who underwent angioplasty of one or more coronary arteries were included in the study. Of these, 202 were treated with SES and the others with EES. The data were collected by a questionnaire through which the annual incidence of coronary stent complications including the occurrence of stent thrombosis (confirmed by re-angiography), the occurrence of acute coronary syndrome leading to hospitalization, the occurrence of vascular myocardial infarction related to the stenting vessel, the need for re-angiography and angioplasty and finally the incidence of cardiac mortality were evaluated. Results: This study showed that the odds ratio of EES thrombosis to SES stent in the unadjusted model is 1.01 (0.06-16.34) and in the adjusted model for confounding variables was equal to 0.80 (0.04-13.35) which in both models, these values were not statistically significant. Conclusion: The findings of the present study indicate that there is no statistically significant difference between the outcomes in the two groups treated with SES and EES release stents.